Management of neurological care during the COVID-19 pandemic - Matías-Guiu, J.; Porta-Etessam, J.; Lopez-Valdes, E.; Garcia-Morales, I.; Guerrero-Solá, A.; Matias-Guiu, J.A. (Neurología (Barcelona, English ed. ), 2020)
The COVID-19 epidemic has led to the need for unprecedented decisions to be made to maintain the provision of neurological care. This article addresses operational decision-making during the epidemic. We report the measures taken, including the preparation of a functional reorganisation plan, strategies for hospitalisation and emergency management, the use of telephone consultations to maintain neurological care, provision of care at a unit outside the hospital for priority patients, decisions about complementary testing and periodic in-hospital treatments, and the use of a specific telephone service to prioritise patients with epileptic seizures. Despite the situation of confinement, neurology departments must continue to provide patient care through different means of operation. Like all elements of management, these must be evaluated. La pandemia de Covid-19 ha supuesto la necesidad de tomar decisiones para mantener la asistencia neurológica, sin precedentes. En este artículo se analiza esa toma de decisiones operativas. Los autores refieren las fórmulas empleadas como son la realización de un plan de reorganización funcional, estrategias para la hospitalización y urgencias, la realización de consultas telefónicas para el mantenimiento de la atención neurológica, la asistencia en un área externa al hospital para pacientes preferentes, las decisiones sobre exploraciones complementarias y tratamientos intrahospitalarios periódicos o implantar un teléfono para la priorización de crisis epilépticas. A pesar de la situación de aislamiento, los servicios de neurología deben mantener la atención de sus pacientes a través de distintas fórmulas operativas, que como cualquier elemento de gestión, deberán evaluarse.